Citizen Innovation as Niche Restoration – A Type of Social Innovation and Its Relevance for Political Participation and Sustainability - Ziegler, Rafael (Journal of Social Entrepreneurship, 2017)
There have been many creative responses to modern economic, political and technological developments and their (un)intended social and ecological consequences. These responses provide the soil for the type of social innovation identified in this article: citizen innovation as niche restoration. It is about civic action that creates novelty by seeking to restore the places and practices citizens already value. Drawing from an in-depth case study on decentralized water management, the concept of citizen innovation as niche restoration is explored, and its implications for political participation and sustainability discussed.
Keywords: Innovation sociale; Participation